SARS-CoV-2 antibody response following COVID-19 vaccination, a longitudinal study - Smita Santosh Chavhan; Prasad Tukaram Dhikale; Balkrishna B Adsul; Chinmay N Gokhale; Aniket R Ingale; Pradnya N Pawar; Nilam Jadhav (Wolters Kluwer Medknow Publications, 2023)
Background: The objective was studying the antibody response following immunization with COVID-19 vaccines. Material and Methods: It was a longitudinal study of healthcare workers (HCWs). Two groups were taken, Group 1 had taken first dose of the COVID-19 vaccine, at least 3 weeks have passed. Group 2 had taken two doses of COVID-19 vaccine and at least 2 weeks have passed. A quantitative test for antibodies to SARS-CoV-2 spike protein was done. Follow-up of both groups was done after 3 months of collection of the first sample. Results: The antibody titre of the 57 HCWs in Group 1, decreased significantly 125 days after the first dose [median = 2,013 U/ml] as compared to the titre 30 days after the first dose of Covishield vaccine[median = 9,965.26 U/ml]. The median interval between two doses of vaccine was 34 days. In Group 2, the antibody titre of the 60 HCWs in Group 2, decreased significantly 114 days after second dose[median = 1,411 U/ml] as compared to the titre 19.5 days after second dose of Covishield vaccine [median = 2,377.5]. There was no significant difference in the antibody titre in follow-up samples of HCWs with and without side effects. Conclusion: The antibody titre decreases after 13 to 17 weeks post the second dose of Covishield vaccination. The decision of the Government of India to increase the interval between two doses of Covishield is justified. Low antibody titre can be the reason for breakthrough infections. The antibody titre was not related to side effects post-vaccination.